2007
DOI: 10.1021/jp070798+
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Viscosity and Host−Guest Association in Aqueous Mixtures of Poly-Cyclodextrin with Azobenzene-Modified Poly(acrylic)acid

Abstract: In aqueous solutions, beta-cyclodextrin (CD) and cyclodextrin-containing polymers (PolCD) associate with azobenzene-modified polyacrylate (AMP). Inclusion complexes in solution of CD (or PolCD) and AMP, and the viscosity of these mixtures, have been studied as a function of the composition of AMP and concentrations of samples. AMPs are random copolymers containing a low fraction of a light-responsive hydrophobic moieties (<10 mol % of 6-[4-alkylamido]phenylazobenzene acrylamide), and a charged hydrophilic unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…For example, some hydrophobically modified water-soluble polymers realized sol-gel transition as a result of the reversible interactions of cyclodextrin and alkyl chains. [5] The assembly and disassembly of polymeric vesicles can be controlled by photosensitive interactions between cyclodextrin and azobenzene compounds. [6] The self-assembly of polyethylene glycol (PEG) and a-cyclodextrins (a-CDs) to form linear pseudopolyrotaxane (PPR), with PEG as the axis and a-CDs as threaded rings, was reported by Harada et al [7] Since the ability of PPR to form physical hydrogels was first reported in 1994, the system has been extensively studied as the hydrogels show very promising uses as biomedicine materials.…”
mentioning
confidence: 99%
“…For example, some hydrophobically modified water-soluble polymers realized sol-gel transition as a result of the reversible interactions of cyclodextrin and alkyl chains. [5] The assembly and disassembly of polymeric vesicles can be controlled by photosensitive interactions between cyclodextrin and azobenzene compounds. [6] The self-assembly of polyethylene glycol (PEG) and a-cyclodextrins (a-CDs) to form linear pseudopolyrotaxane (PPR), with PEG as the axis and a-CDs as threaded rings, was reported by Harada et al [7] Since the ability of PPR to form physical hydrogels was first reported in 1994, the system has been extensively studied as the hydrogels show very promising uses as biomedicine materials.…”
mentioning
confidence: 99%
“…Macromolecules that are light‐sensitive have potential applications in controlled drug‐delivery and sol–gel materials. Pouliquen et al48 have studied the binding of azobenzene‐modified polyacrylate (AMP) to β‐cyclodextrin (CD) and CD‐containing polymers (PolCD) in aqueous solution and their photoresponse by CE and UV–vis spectrometry. They found that AMP interacts more tightly with PolCD than any CD monomer tested including α‐CD, β‐CD, and hydropropyl‐β‐CD.…”
Section: Discussionmentioning
confidence: 99%
“…Doi et al recently reported the dimerization of trans carboxyl styrylpyrene under 455 nm visible light, which could be efficiently reversed by irradiation with 340 nm UV light. [65] Thus, many designs for photoresponsive hydrogels based on azobenzene-CD host-guest interaction were invented, as reviewed lately. [59][60][61] In addition, photoinduced exchange reactions, such as disulfide exchange chemistry and allyl sulfide/thiol exchanges, have been adopted in the design of lightresponsive hydrogels.…”
Section: Molecular Mechanismsmentioning
confidence: 99%